Conducta obstétrica en primigesta de 14 años de edad con embarazo gemelar de 34.4 semanas con preeclampsia leve. - Ruela Hernández, Mariuxi Isamar (2022)
Twin pregnancy or múltiple pregnancy represents an obstetric risk both for the mother and for the fetuses because it is a high-risk pregnancy, over time it is more common for this type of pregnancy to occur for different reasons such as older age of the mother, multiparity, race, genetic inheritance, but it is very rare for this type of pregnancy to occur in an adolescent. Being a high-risk obstetric pregnancy, these twin pregnancies usually develop different complications such as preeclampsia, anemia, threat of premature birth, with hypertensive disorders being one of the main causes of maternal death. This case, which was presented at the Nicolas Cotto Infante Basic Hospital, was followed up throughout the evolution of the pregnancy, with prenatal controls, ultrasound, monitoring of laboratory tests, which determine the state of the mother and the fetuses. This clinical case presents the different situations that health professionals face due to the adverse situations that occur during pregnancy.